2020
DOI: 10.1109/jiot.2020.2976114
|View full text |Cite
|
Sign up to set email alerts
|

A Local Communication System Over Wi-Fi Direct: Implementation and Performance Evaluation

Abstract: Wireless communication demands increase sharply with the explosive growth of mobile devices. The communications mainly depend on the infrastructure-based networks, e.g., WLANs and cellular networks. However, such wireless connections may be unavailable in crowded areas (e.g., concert and conference hall) or interrupted by infrastructure failures caused by earthquake or tsunami. These promote the evolution of local communication systems over device-to-device communication, such as Bluetooth and Wi-Fi Direct (WF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Wi-Fi Direct is a Device-to-Device(D2D) wireless communication technology developed by Wi-Fi Alliance [11]. The Network Interface Controller (NIC) of the smartphone, which supports this technology, is logically separated into two interfaces [9].…”
Section: Wi-fi Directmentioning
confidence: 99%
See 1 more Smart Citation
“…Wi-Fi Direct is a Device-to-Device(D2D) wireless communication technology developed by Wi-Fi Alliance [11]. The Network Interface Controller (NIC) of the smartphone, which supports this technology, is logically separated into two interfaces [9].…”
Section: Wi-fi Directmentioning
confidence: 99%
“…Many studies have emerged an interest in establishing ad hoc network using Wi-Fi Direct technology [8][9][10], but some of them did not mention how to build the network and how to distribute roles between smartphones [11]. Furthermore, the adoption of broadcasting in transmission of data within the network [10] [9], is unreliable data transmission.…”
Section: Introductionmentioning
confidence: 99%
“…can establish a direct Wi-Fi connection without using a wireless access point for exchanging health data. In the same context, Fuliang et al (2020) [26] also did a research in Wi-Fi Direct and they proposed a real-time data transmission system by using Wi-Fi Direct for the transfer of healthcare data. The results of the research showed that the healthcare data are transported with greater reliability through Wi-Fi Direct than through Wi-Fi.…”
Section: -1-2-short-range Distance Health Information Exchange Techniquesmentioning
confidence: 99%
“…To this context, it has been already defined that Apple generally supports a short list of Bluetooth profiles, such as the Hands-Free Profile (HFP), The Phone Book Access Profile (PBAP), or the Advanced Audio Distribution Profile (A2DP), which however cannot serve the purposes of the D2D protocol. Among the supported Bluetooth profiles, the Bluetooth PAN profile is considered as the most appropriate for the current D2D protocol specification for Apple devices, since the Bluetooth SPP profile cannot be supported by the latter due to Apple's development restrictions [26]. Consequently, the overall study results that in the case that the D2D protocol would not be considered to be vendor specific but would only be considered to be efficient and effective, then the Bluetooth SPP profile should be the only choice among the different Bluetooth profiles.…”
Section: -Conclusionmentioning
confidence: 99%
“…The key point localization is the foundation of face recognition and other research, and the application scenarios are very broad [11]. As shown in Figure 1, the researchers have proposed many algorithms for face key point localization and achieved good results in related fields, but in practical applications, faces are often affected by various internal and external factors such as expression, posture, lighting, and occlusion, making it very difficult to achieve accurate face key point localization, which remains a great challenge [12]. This topic will address the design and optimization of the face key point positioning model and its application in mobile based on the actual application scenarios.…”
Section: Introductionmentioning
confidence: 99%